QALYs, DALYs and value of human life - Tzermpinou, Anthi (Bioethica, 2022)
This study is focused on the health assessment through the measures currently used to make decisions on the allocation of ”scarce resources”. Particular attention is given to quality adjusted life years, disability-adjusted life years and willingness to pay. This publication aims to contribute to a better understanding of the individuality of situations that small groups of people may experience in their patient journey, the difficulties that metrics face when quantifying subjective measures in evaluating these situations as well as to examine the issue from a bioethical point of view. Building on previous research, that cast doubt on the value of summary health measures such as the measures of QALY and DALY, in improving population health, and identifying additional challenges, it is concluded that solely these measures are not ethically acceptable to be used while the involvement of bioethicists is recommended in the decision-making process.